DFT study of iron impurity in ZrSiO4 - Stashans, A. (2013)
Density functional theory (DFT) and generalised gradient approximation have been employed to study effects produced by chromium dopant in the tin dioxide. Hubbard-like term (DFT+U method) has been introduced to provide better description of magnetic moments, internal degrees of freedom and electronic band structure features. Results on microstructure, electronic properties and magnetic behaviour of the material are discussed for different dopant concentrations. A peak within the band-gap region has been found. It grows up in intensity for higher impurity concentrations. Hybridization between the Cr 3 d and O 2 p states within the upper valence band, detected in our study, might have an influence on magnetic behaviour of the Cr-doped SnO2 materials. © 2014 Springer Science+Business Media New York.